Influence of the synthesis conditions on the microstructural, compositional and morphological properties of graphene oxide sheets. Issue 14 (1st October 2020) - Burresi, E.; Taurisano, N.; Protopapa, M.L.; Latterini, L.; Palmisano, M.; Mirenghi, L.; Schioppa, M.; Morandi, V.; Mazzaro, R.; Penza, M.
Abstract: In this paper we report about the synthesis and characterization of graphene oxide (GO). We monitor the effects of the different synthetic processes on the morphological and structural properties of the materials. A modified Hummers' method is adopted to obtain GO powder; H2 SO4 is employed as intercalating agent, to increase the distance between graphitic layers, while KMnO4 is used as oxidizing reagent for introducing the oxygen functionalities in the graphitic structure. The oxidized graphite powder is treated in acid solution; different washing cycles are applied. The recovered powders are dispersed in aqueous solution and sonicated for 30 min or 60 min, respectively. Subsequently, these solutions are deposited on Si and SiO2 (317 nm)/Si substrates by means of dip coating. GO powders, GO solutions and GO on substrate are characterized through several analytical and spectroscopic techniques. These analyses reveal that the sonication time and the washing procedure of the samples can influence the structure and the morphology of the graphene oxide flakes. Moreover, when KOH is employed as alkaline agent in a chemical reducing treatment of the GO powder before sonication, a considerable alteration of the native structure of graphene oxide is observed. The detailed characterization indicates that the properties of the GO samples are strongly influenced by the chemical and physical treatments to which it is subjected.